A Comprehensive Approach to Clinical Decision Support in the Return of Genome Informed Risk Assessments to Primary Care Pediatricians - Karavite, Dean; Terek, Shannon; Connolly, John J.; Harr, Margaret; Muthu, Naveen; Hakonarson, Hakon; Grundmeier, Robert W. (Applied Clinical Informatics, 2025)
Background Primary care pediatricians play an important role in genetic testing, including referrals, test ordering, responding to results, assessing risk, treatment, and managing care. As genetic testing rapidly evolves to include new tests identifying patients at risk for certain conditions, alert-based clinical decision support is insufficient in assisting pediatric primary care providers in working with patients, parents, genetics, and other specialties. Supporting pediatricians in the return of these results requires addressing gaps in genetics training and integrating genetics into practice with education, information resources, and specialized tools.Objectives This study aimed to capture requirements for developing systems and processes to support primary care pediatricians in the return of genome-informed risk assessments.Methods We performed a requirements analysis to inform the design of clinical decision support tools and processes for pediatric providers of patients who received a genome informed risk assessment, a novel test that combines polygenic risk scores with patient and family histories to deliver a risk assessment for common medical conditions. We developed an interview guide consisting of scenario presentations, questionnaires, and semi-structured questions to elicit provider responses on a broad set of requirements to manage results with patients and caregivers.Results Twenty providers from 10 primary care pediatric practices within a single health system participated in the study. The findings demonstrated that providers feel responsible to be involved in the process of returning results but require a support system that integrates education, provider and patient information resources, effective communication with genetics, and electronic health record decision support tools that can accommodate a range of clinical scenarios and provider workflow preferences.Conclusion Supporting providers with the return of genetic testing results such as the genome informed risk assessment requires a comprehensive approach to decision support consisting of education, communication, and a comprehensive and integrated set of electronic health record tools.
Keywords: clinical decision support; requirements analysis and design; workflows and human interactions; genetics; ambulatory care/primary care; pediatrics